Nocardia rubra cell-wall skeleton activates an immune response in cervical tissue via stimulating FPR3 to enhance dendritic cell-mediated Th1 differentiation - Guo, Qianyu; Chen, Wei; Sun, Junyi; Zhao, Chunfang; Bai, Xue; Zhang, Yanan; Liu, Ke; Zhang, Lei; Shao, Suxia (Frontiers in Immunology, 2023)
Nocardia rubra cell wall skeleton (Nr-CWS) has proven to be a successful medicine for therapy of cervical human papillomavirus infection. The mechanism of action of Nr-CWS is unclear but may involve a stimulatory effect on the host immune system. We previously found that CD4+ T cells were increased in cervical tissue after Nr-CWS treatment. Microarray data from these cervical tissues revealed the significant upregulation of formylated peptide receptor 3 (FPR3). This study aimed to explore the role of Nr-CWS in immunomodulatory based on these findings. Examination of CD4+ T cell subsets in cervical tissue from patients who received Nr-CWS revealed substantial increases in Th1 cytokines and transcription factors. The regulatory effects of Nr-CWS on the function and phenotype of dendritic cells (DCs) were assessed in comparison with the traditional DC maturation inducer lipopolysaccharide (LPS). Similar to LPS, Nr-CWS potently induced DC maturation and interleukin-12 (IL-12) secretion. Differentiation of T cells induced by Nr-CWS stimulated DCs was assessed using the mixed lymphocyte reaction assay. Significant differentiation towards Th1 was evident. Finally, FPR3 expression in DCs in response to Nr-CWS and LPS was measured. Nr-CWS potently upregulated FPR3 expression, while the LPS did not. Silencing FPR3 in DCs reduced Nr-CWS-induced IL-12 production and Th1 cell polarization in co-cultured T cells. The collective findings indicate that Nr-CWS may target FPR3 on the surface of DC cells and activate a Th1-type immune response. The findings clarify the basis of the antiviral immune effects of Nr-CWS on human papillomavirus.